Transformasi Konflik Pemerintah Daerah Dalam Kekerasan Seksual: Transformasi Konflik Pemerintah Daerah Dalam Kekerasan Seksual - Adita Nur Karismah; Adinda Alya Ramadhan; Aida Dinda Putri; Aldy Syahputra (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
sexual violence is an important national issue. News in the mass media both print and electronic media on this issue shows the high level of sexual violence in Indonesia, sexual violence is an important national issue. News in the mass media both print and electronic media on this issue shows the high rate of sexual violence in Indonesia there, Literature study is a method used to collect data or sources related to topics raised by researchers in a study Jakarta government is also working with civil society organizations to strengthen the referral system and coordination in the handling of cases of sexual violence Jakarta government also conducts case reporting mechanisms that are more accessible to the public in this case, The government of DKI Jakarta seeks to transform the conflict by promoting a collaborative and participatory approach by involving civil society and victims in decision-making. This is a very important key to strengthen the capacity between authorities and service providers to achieve the improvement of a system to deal with cases of sexual violence.